The support gap: New teachers' early experiences in high-income and low-income schools - Johnson, Susan Moore; Kardos, Susan M.; Kauffman, David; Liu, Edward; Donaldson, Morgaen L. (Education Policy Analysis Archives, 2004)
In this article, the authors consider three sources of support for new teachers—hiring practices, relationships with colleagues, and curriculum—all found in earlier research to influence new teachers’ satisfaction with their work, their sense of success with students, and their eventual retention in their job. They find that a "support gap" exists: new teachers in low-income schools are less likely than their counterparts in high-income schools to experience timely and information-rich hiring, to benefit from mentoring and support by experienced colleagues, and to have a curriculum that is complete and aligned with state standards, yet flexible for use in the classroom. Such patterns of difference between high-income and lowincome schools warrant careful consideration because they reveal broad patterns of inequity, which can have severe consequences for low-income students. Survey data for this study were collected from random samples of teachers in five states. One survey, focusing on hiring practices and teachers’ relationships with colleagues, was administered to 374 first-year and secondyear teachers in Florida, Massachusetts, and Michigan. A second survey, focusing on curriculum, was administered to 295 second-year elementary school teachers in Massachusetts, North Carolina, and Washington. The inequitable patterns of support for teachers reported here have important implications for the work of state policymakers, school district administrators, and principals. The authors describe these and offer recommendations for policy and practice in the conclusion.